Organizational resources and intrapreneurial activities: An international study (2013)
Purpose: The main purpose of this paper is to analyse the influence of resources and capabilities on the probability of becoming an intrapreneur, using resource-based theory as a conceptual framework. Design/methodology/approach: The research uses a logistic regression analysis and data from the Global Entrepreneurship Monitor (GEM) for 39 countries and 36,325 individuals. Findings: Results show that companies' resources and capabilities are a key factor in the development of intrapreneurship. Entrepreneurial resources and capabilities, such as previous entrepreneurial experience, entrepreneurial competences and the ability to detect business opportunities, influence intrapreneurial behaviour. Research limitations/implications: The contributions of this research are both conceptual (advancing corporate entrepreneurship theory) and practical (relating to the design of policies to foster intrapreneurial activities). Originality/value: The importance of entrepreneurship for social and economic growth is generally accepted. In addition, intrapreneurship or corporate entrepreneurship is recognized as one of the key elements for organizational development. Despite this, there are very few empirical articles using an explicit and integrated theoretical framework such as resource-based theory for the analysis of intrapreneurial phenomenon. © Emerald Group Publishing Limited.